Artesanato indígena brasileiro: análise da dimensão econômica da sustentabilidade - Briedis, Franciele de Carvalho (2023)
Handicraft production is historically widespread among indigenous communities. But, even with dedication to this cultural craft by the native Brazilian peoples, it is clear, due to their high degree of poverty, that the income from their trade can be little expressive. In this way, the present research aims to analyze the Brazilian indigenous crafts focusing on the economic dimension of sustainability. The method used was exploratory and comparative research, of an applied nature, carried out through documentary research as a form of technical procedure. The documentary source of data comes from the Brazilian Handicraft Registration Information System (SICAB), this system was created by the Brazilian Handicraft Program (PAB), and includes a special session for traditional communities, which allowed access to productive data relating to the Brazilian indigenous community. In this context, based on parameters such as family income range, gender, geographic distribution, manufactured products, technique and raw material used, place of production, among others, it was possible to carry out data crossings and comparisons, relating the family income ranges with productive characteristics. One of the points identified in the results was the North region of Brazil as proportionally the most engaged in the number of indigenous people registered in SICAB, with the largest number of instructors in artisanal technique courses, participation in training, participation in commercial events, exports, and access to finance for its production. The Northeast region of Brazil stood out with leadership in income rates above one minimum wage for indigenous people who have handicrafts as their main activity. On the other hand, the South region drew attention due to the lower proportion of these income indices. The analyzes and information presented will be useful to the academy, by providing literature that is still little explored in the field. In addition, it adds contributions to society, with information that can be used to base strategic decisions on public policies, entrepreneurs, and the indigenous artisan community itself.